The Presence of Aedes Aegypti Larvae and the Occurrence of Dengue Fever (DHF) In Beti Village, South Indralaya District, Ogan Ilir Regency (International Journal of Scientific Research and Management (IJSRM), 2022)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that can be fatal. There were 117 DHF cases in Ogan Ilir Regency in 2018. The presence of Aedes aegypti and community behavior in mosquito breeding eradication are critical for dengue vector larvae survival. The purpose of this research is to establish a link between the presence of Aedes aegypti larvae and the presence of DHF in Beti Village, South Indralaya District, Ogan Ilir Regency, South Sumatra Province. This was an observational cross-sectional study with 49 randomly selected resident houses. The presence of larvae in water reservoirs was used to collect data, whereas the incidence of DHF was obtained through questionnaire interviews with respondents. For statistical analysis, the chi-square test was used. According to the findings of the study, 38.8 percent of respondents have a history of DHF. The majority of the larvae were discovered in water reservoir buckets. There is a link between the type of Aedes aegypti breeding and the incidence of DHF (p-value of 0.001), Aedes aegypti presence and the incidence of DHF (p-value of 0.005), and PSN behavior and the incidence of DHF (p-value of 0.005). (p-value of 0.001). Beti Village residents are advised to take preventive and vector control measures to reduce their risk of contracting dengue disease. Residents must become more involved in cleaning water reservoirs in and around their homes on their own.